The Relationship Between Physical Activity And Macronutrient Intake With The Menstrual Cycle In Members Of The Surabaya State University Tennis Club - Laila Al Istighfara; Satwika Arya Pratama; Cleonara Yanuar Dini; Ratna Candra Dewi (International Journal of Health Engineering and Technology, 2026)
The menstrual cycle is an important indicator of reproductive health, hormonal balance, and energy sufficiency in women who are physically active. Irregular menstrual cycles may be related to an imbalance between physical activity and nutrient intake, particularly among college students who actively participate in sports. This study aimed to determine the relationship between physical activity and macronutrient intake and the menstrual cycle among members of the Surabaya State University Tennis Club. This study used a quantitative cross-sectional design with a sample of 41 respondents selected through total sampling. Data were collected using the IPAQ-LF, a 3×24-hour food recall, and a menstrual cycle questionnaire, and were analyzed using the Fisher-Freeman-Halton Exact Test. The results showed that the majority of respondents engaged in vigorous physical activity (58.5%), had insufficient carbohydrate intake (85.4%), insufficient protein intake (90.2%), excessive fat intake (41.5%), and a normal menstrual cycle (63.4%). The analysis revealed no significant association between physical activity and the intake of carbohydrates, protein, and fat and the menstrual cycle. The conclusion of this study is that physical activity and the intake of macronutrients are not significantly associated with the menstrual cycle.